Applications of Engineered Particulate Systems in Agriculture and Food Industry - Aarthi Narayanan; Parvesh Sharma; Brij M. Moudgil (KONA Powder and Particle Journal, 2013)
The development of nanotechnology for advances in various sectors like health, consumer products has paved way for possible applications in agriculture and food industries. Antimicrobial agents (e.g., silver, titanium dioxide), nano-bio pesticides (hydrophobic silica), smart delivery systems (polymeric nanoparticles) provide promising enhancement or alternatives to the conventional crop protection strategies, which are primarily based on applying chemicals in solid, liquid or suspension forms. Nanotechnology approaches in food industry can impart properties such as resistance to gas penetration, increased tensile strength and enhanced absorption of nutrients leading to novel food packaging and processing materials. Despite these features, the usage of nanotechnology is still limited, owing to the lack of proper toxicity evaluation data. Understanding the risks and taking appropriate measures to mitigate them will significantly enable nanotechnology advances targeting to agriculture and food industries. In this paper, we have reviewed some of the recent research and development efforts that have been carried out in nanotechnology for its potential applications in agrifood sector. More specifically, nanotechnology approaches mediated by particle technology advances are reviewed.